"...in our time..." A Statement on Relations between the Presbytery of Chicago and the Jewish Community in Metropolitan Chicago - at First Presbyterian Church of Lake Forest, IL, Presbytery of Chicago Meeting in Presbytery Assembly, 21 November 2015 (Studies in Christian-Jewish Relations, 2016)
No abstract is available.